LHC multijet events as a probe for anomalous dimension-six gluon interactions - Krauss, Frank; Kuttimalai, Silvan; Plehn, Tilman (Arxiv, 2017)
Higher-dimensional multi-gluon interactions affect essentially all effective Lagrangian analyses at the LHC. We show that, contrary to common lore, such operators are best constrained in multi-jet production. Our limit on the corresponding new physics scale in the multi-TeV range exceeds the typical reach of global dimension-6 Higgs and top analyses. This implies that the pure Yang-Mills operator can safely be neglected in almost all specific higher-dimensional analyses at Run II.
Gesehen am 11.08.2017